PERENCANAAN PENGGANTIAN JEMBATAN JUWET KABUPATEN PEMALANG - Andhy Satriya Wardhana; Mohamad Irzam Hasani; Moga Narayudha; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2015)
Juwet Bridge is located approximately one kilometer to the south of Comal Bridge Pemalang District is one of the alternative bridges used when the Comal Bridge collapsed. In this final Juwet Bridge which has a width of only 3 meters is designed with a larger capacity and functioned as an alternative pathway Comal Bridge. Planning on aspects of traffic using a design life of 20 years with the growth of the vehicle based on a linear regression of 642 veh / year and using two scenarios, there are normal conditions (2 Comal Bridge function) and incidental conditions (only 1 Comal Bridge functioning). Initial planning, the alternative pathway using a type 2/2 UD. In normal conditions, the distribution of traffic flow 70% for Comal Bridge and 30% for Juwet Bridge produce a degree of saturation (DS) under 0.75 over the life of the plan. In the incidental conditions, the distribution of traffic flow 60% for Comal Bridge and 40% for Juwet Bridge, DS value is 0.81. Assuming then use 2/2 type UD with 8 meters wide still used. New Juwet Bridge continue to use steel as the structure and the upper structure of reinforced concrete for the structure underneath. Planned implementation within 8 months at a cost of Rp. 36.4 billion. In this final project scope of the planned bridge elements include work for the overall structure of the bridge and approach bridge. Given this new Juwet Bridge when congestion occurs on the Pantura line around Comal Bridge, the bridge is able to be an alternative pathway in servicing and reducing the burden of most of the traffic flow on the Pantura line.